Modeling of p-aminophenol compounds as analgesic antiinflammatory based on biologic activity and structure relationship - ., Pudjono; Susilowati, Sri Sutji; ., Rehana (Indonesian Journal of Pharmacy, 2011)
This  research  aim  was  to  find  out  the  new  compounds model  of  paminophenol derivates which have analgesic anti-inflammatory activity based on structure  and  biologic  activity  relationship  analysis  by  computation  methods. Seventeen  compounds  of  p-aminophenol  derivates  were  used  in  this  research, and  six  compounds  known  its  analgesic-antiinflammatory  activity  were  used  for determine  QSAR  equation  model.  This  research’s  result  was  a  QSAR  equation that  can  be  using  for  synthesis  the  higher  activity new  compound  of  paminophenol. Key  words  :  p-aminophenol  compounds,  analgesic  anti-inflammatory activity,  structure and activity relationship, QSAR equation, computation methods